2020
DOI: 10.1093/ndt/gfaa271
|View full text |Cite
|
Sign up to set email alerts
|

Mortality analysis of COVID-19 infection in chronic kidney disease, haemodialysis and renal transplant patients compared with patients without kidney disease: a nationwide analysis from Turkey

Abstract: Background Chronic kidney disease (CKD) and immunosuppression, such as in renal transplantation (RT), stand as one of the established potential risk factors for severe coronavirus disease 2019 (COVID-19). Case morbidity and mortality rates for any type of infection have always been much higher in CKD, haemodialysis (HD) and RT patients than in the general population. A large study comparing COVID-19 outcome in moderate to advanced CKD (Stages 3–5), HD and RT patients with a control group of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
209
6
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(250 citation statements)
references
References 34 publications
25
209
6
10
Order By: Relevance
“…In agreement with findings from other series, our study shows that ICU access [ 28 , 29 ] and CKD predict mortality [ 30 , 31 ]. Interestingly, transfusion need is not higher in patients administered with prophylactic LMWH doses, therefore confirming that this scheme is safe.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with findings from other series, our study shows that ICU access [ 28 , 29 ] and CKD predict mortality [ 30 , 31 ]. Interestingly, transfusion need is not higher in patients administered with prophylactic LMWH doses, therefore confirming that this scheme is safe.…”
Section: Discussionsupporting
confidence: 93%
“…They also found that there was a substantial benefit to the recipient following living-donor kidney transplantation. In a multicenter study from Turkey, Ozturk et al [ 4 ] compared the mortality of the patients with CKD and HD and found no difference between recipients and the control group; however, patients with HD and CKD had higher mortality. Craig-Schapiro et al [ 2 ] compared the clinical results of COVID-19 in patients with waitlisted and recipients, and they showed that waitlisted patients had a higher risk for hospitalization and mortality, and declared that COVID-19 had a dramatic impact and took the patient’s opportunity for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis from the US, Europe, and China, the prevalence of heart disease was 37% and CKD 27% [39] . In a multicenter study from Turkey among patients with CKD, 21.9% admitted to ICU, and 14.2% died [40] . The interactions between CKD and diabetes in COVID‐19 may render these patients highly vulnerable to death.…”
Section: Discussionmentioning
confidence: 99%